Peningkatan Tata Kelola Usaha Fotocopy Mitra Abadi Melalui Penyusunan Laporan Kas dan Stok Barang - Naya Klaresa; Stefina Putri; Fitri Oktariza; Regina Vella Loves; Lasti Yossi Hastini; Ratnawati Raflis; Triska Marvidola; Nurweni Putri (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
Fotokopi Mitra Abadi is an example of a micro-enterprise whose financial and inventory management had not been properly documented. Previously, the owner relied solely on memory to track cash flow and merchandise stock. This issue was addressed through our community service program. We developed easy-to-use financial and inventory report formats, then trained the owner directly. Four stages were carried out in the field: observation, designing the report format, conducting training (using both handwritten and digital methods via Microsoft Excel), and evaluating the owner's understanding through Q&A sessions. This mentoring program produced real results—the owner's understanding jumped sharply, with the pretest score of only 10% rising to 80% on the posttest. To keep things simple, the cash book was designed to be as straightforward as possible. It includes key columns such as date, transaction details, cash in and cash out, and final balance calculations, reinforced with periodic report summaries. Inventory management, meanwhile, is handled through a stock control sheet containing item names, units, records of incoming and outgoing goods, and remaining stock, operating on the First In First Out (FIFO) method.